PERANAN KEPEMIMPINAN MANAJEMEN PENDIDIKAN - Sukatin, Sukatin; Puspitasari, Dian; Zainab, Heni; Khairunnisa, Nabilla; Rhamadhan, Gilang (Department of Islamic Education Management, 2022)
Abstract: Efforts to improve education management leadershipThis paper was made to find out the form in improving education management leadership with library research methods by collecting various sources of writing to obtain specific conclusions, from this research it can be seen that the role of management leadership has an important role to improve the development of the quality of education.Abstrak: Peranan kepemimpinan manajemen pendidikan Tulisan ini dibuat untuk mengetahui bentuk upaya dalam meningkatkan kepemimpinan manajemen pendidikan dengan metode penelitian kepustakaan dengan mengumpulkan berbagai sumber sumber tulisan untuk mendapatkan kesimpulan secara khusus dari penelitian ini dapat diketahui bahwa peran kepemimpinan manajemen memliki peranan penting untuk meningkatkan pengembangan mutu pendidikan.